A noble bimetal oxysulfide CuVOS catalyst for highly efficient catalytic reduction of 4-nitrophenol and organic dyes. Issue 55 (7th October 2019) - Sun, Huizhi; Zelekew, Osman Ahmed; Chen, Xiaoyun; Guo, Yuanbo; Kuo, Dong-Hau; Lu, Qingxin; Lin, Jinguo
Abstract : A novel Cu V OS catalyst was successfully synthesized by a facile method. The Cu V OS with optimum amount of N2 H4 had higher catalytic activity. Abstract : A novel copper–vanadium bimetallic oxysulfide (Cu V OS) nanoparticle catalyst was successfully synthesized by a facile method. The samples were characterized by X-ray photoelectron spectrometry (XPS), X-ray diffractometry (XRD), field-emission scanning electron microscopy (FE-SEM), UV-Vis diffuse spectroscopy (DRS), Fourier transform infrared spectroscopy (FTIR), and N2 adsorption–desorption isotherms. In order to check the catalytic efficiencies toward reduction reaction, 4-nitrophenol (4-NP) and other organic dyes such as rhodamine-B (RhB), methylene blue (MB), and methyl orange (MO) were used. The results showed that the Cu V OS prepared in the presence of a suitable amount of N2 H4 during the synthesis of the nanoparticles exhibited the fastest reduction capabilities by using NaBH4 as a reducing agent. It was demonstrated that a 100 mL 4-NP (20 ppm) solution was completely reduced by 5 mg Cu V OS-3 within 2 min. Moreover, the complete reduction of 100 mL of MO, RhB, and MB solutions of 100 ppm was also achieved by 5 mg Cu V OS-3 within 2 min, 6 min, and 5 min, respectively. Hence, the Cu V OS is an efficient catalyst for reducing 4-NP and organic dyes and can have great potential for industrial application.